(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The professional growth of school English teachers is directly linked to the quality of pedagogical assessment methods. Effective assessment not only measures current competencies but also guides future professional development. This paper explores theoretical and practical methods for improving the effectiveness of assessing the pedagogical skills of school English teachers. The study draws on contemporary approaches in educational measurement, language pedagogy, and teacher evaluation frameworks. Recommendations are proposed for integrating formative, peer-based, and digital assessment tools to ensure comprehensive evaluation and sustainable teacher growth